2003
DOI: 10.1038/sj.bjp.0704997
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of functional M3‐muscarinic receptors in ventricular cardiomyocytes of adult rats

Abstract: 1 Muscarinic receptors (M-receptors) in the mammalian heart are predominantly of the M 2 -subtype. The aim of this study was to ®nd out whether there might exist an additional myocardial non-M 2 -receptor. 2 For this purpose, we assessed, in adult rat isolated ventricular cardiomyocytes, carbacholinduced [ 3 H]-inositol phosphate (IP) formation, and its inhibition by M-receptor antagonists. 3 Carbachol (10 77 ± 10 73 mol l 71 ) increased IP-formation (maximal increase: 14+3% above basal, n=6). This increase wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 19 publications
1
32
1
Order By: Relevance
“…After activation of cardiac M 2 receptor in atrium, the ␤␥ subunit of the G i protein directly activates the inwardly rectifying muscarinic K ϩ channel, i.e., the ACh receptor-operated K ϩ channel (Yamada et al, 1998). Although the M 2 receptor is a predominant muscarinic receptor subtype presented in heart, the presence of low levels of non-M 2 muscarinic receptors including M 3 receptor subtype was reported (Pönicke et al, 2003;Wang et al, 2004;Myslivecek et al, 2008). Muscarinic M 3 -receptor blockade by 4-DAMP almost completely abolished the positive response to CCh with slight inhibition of the negative response in the present study.…”
Section: Discussionsupporting
confidence: 42%
“…After activation of cardiac M 2 receptor in atrium, the ␤␥ subunit of the G i protein directly activates the inwardly rectifying muscarinic K ϩ channel, i.e., the ACh receptor-operated K ϩ channel (Yamada et al, 1998). Although the M 2 receptor is a predominant muscarinic receptor subtype presented in heart, the presence of low levels of non-M 2 muscarinic receptors including M 3 receptor subtype was reported (Pönicke et al, 2003;Wang et al, 2004;Myslivecek et al, 2008). Muscarinic M 3 -receptor blockade by 4-DAMP almost completely abolished the positive response to CCh with slight inhibition of the negative response in the present study.…”
Section: Discussionsupporting
confidence: 42%
“…An immunohistochemical study indicated that M 3 receptors are present on cardiomyocytes (Wang et al, 2001). In addition, M 3 receptor-mediated increases in inositol phosphate formation have been observed with dispersed cardiomyocytes (Pönicke et al, 2003;Myslivecek et al, 2008). Alternatively, because M 3 receptor-mediated positive inotropic effects were abolished by treatment with 1% Triton X-100 or indomethacin, it has been proposed that M 3 receptors present on the endocardial endothelium stimulate the production of endogenous prostaglandins eliciting positive inotropic actions (Tanaka et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, the M 2 receptor is not the only muscarinic receptor subtype present in the heart (Wang et al, 2004). Pharmacological, biochemical, immunohistochemical, and molecular biological studies using whole heart tissues or isolated cardiomyocytes indicate that the heart, es-pecially cardiomyocytes, also expresses low levels of non-M 2 muscarinic receptors, including the M 1 and M 3 receptor subtypes (Gallo et al, 1993;Sharma et al, 1996;Hardouin et al, 1998;Hellgren et al, 2000;Wang et al, 2001Wang et al, , 2004Krejcí and Tucek, 2002;Pönicke et al, 2003;Willmy-Matthes et al, 2003;Pérez et al, 2006;Myslivecek et al, 2008).…”
mentioning
confidence: 99%
“…These effects are particularly strong in pacemaker and atrial tissues. The M 2 muscarinic receptors prevail in the mammalian myocardium, although some M 3 receptors are also present and physiologically active (Pönicke et al, 2003;Wang et al, 2007). The even-numbered muscarinic receptors, including M 2 , are coupled to G i proteins and act via inhibition of adenylate cyclase and a subsequent decrease in cellular cAMP content (Dhein et al, 2001).…”
Section: Discussionmentioning
confidence: 99%